A dual stimuli-responsive and safer controlled release platform of pesticide through constructing UiO-66-based alginate hydrogel. (May 2021) - Feng, Pu; Huang, Guohuan; Fan, Chaoran; Li, Yanming; Xu, Chuanhui; Fu, Lihua; Lin, Baofeng
Abstract: Agricultural chemical residue in the environment is one of the biggest concerns for biosafety and human health worldwide. Here, we develop a carrier for pesticides by the chemical combination of UiO-66 and sodium alginate (Alg). When clothianidin (CTD) was encapsulated in UiO-66/Alg, they showed the ability to act as controlled-release pesticides with double stimuli-responsive. Although only 62.74% of CTD was released at 27 °C in 144 h, 93.52% was released at 45 °C at the same time, and the release could be tuned by adding phosphate at the time of greatest requirement. Moreover, the UV-irradiating stability of CTD in UiO-66/Alg was >3.5 times greater than for free CTD, which combined with the outstanding biosafety of UiO-66/Alg-CTD illustrates its potential for development as a bio-friendly, stable and intelligent carrier of pesticides to improve the utilization efficiency of pesticides. Highlights: UiO-66/Alg-CTD pesticide carrier is prepared by chemical crosslinking. UiO-66/Alg-CTD has a dual stimulus-response to temperature and phosphate. UiO-66/Alg-CTD has good biological safety and no harm to soil.